Konseling Islam untuk Meningkatkan Strategi Coping Korban Bencana Kebakaran di Kota Samarinda - Suryani, Siti Indah; Hasanah, Maulita; Hidayati, Di Ajeng Laily (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
Fire is a form of disaster that often occurs in the city of Samarinda. The densely populated location and construction of residential houses made from wood often exacerbate the magnitude of the fire which is mostly caused by short-circuiting of electricity. One of the impacts that befell the fire victims is psychological trauma. The trauma impulsively raises coping strategies in the individual. This study aims tosee how the coping strategy of fire victims in overcoming the problems that befall them after the disaster. This study uses descriptive qualitative method with three data collected techniques, namely observation, interview and documentation. The results of the study prove that there are supporting and inhibiting factors for coping strategies for victims of fire disasters in Samarinda City. Supporting Factors Victim coping strategies are spiritual beliefs, material assistance from State institutions, and support from the victims' social environment. On the other hand, the inhibiting factor of the fire victim coping strategy is the uneven distribution of aid patterns and the absence of experts in the field of counseling or psychology. On the other hand, the government also has not provided experts such as psychologists or counselors who are tasked with dealing with psychological crises experienced by post-disaster victims. The absence of experts in dealing with the conditions of the fire victims crisis can be taken over by experts in Islamic counseling to apply Islamic counseling to enhance the coping strategies of victims of fire disasters in Samarinda City.